Endovascular Management of Internal Carotid Artery Pseudoaneurysm Secondary to Pediatric Deep Neck Space Infection: A Case Report and Review of Literature - Rengarajan Rajagopal; Smily Sharma; Meenu Bagarhatta; Sarbesh Tiwari; Rajeev Bagarhatta (The Arab Journal of Interventional Radiology, 2021)
Pseudoaneurysms of extracranial internal carotid artery (ICA) are rare in children. Main causes include trauma, iatrogenic causes, and neck space infection. Prompt diagnosis and management is vital, in view of life-threatening complications like fatal airway hemorrhage and stroke. Endovascular management has currently become the preferred treatment strategy due to its minimally invasive nature and lower complication rates. We report a rare case of mycotic pseudoaneurysm of extracranial ICA in a 4-year-old child as a complication of neck space infection, which was successfully managed with endovascular parent artery occlusion.